Tepung rumput laut Sargassum sp. sebagai pakan tambahan bagi ikan kerapu cantang (Epinephelus fuscoguttatus-lanceolatus) - Tosi, Ina Damilna; Ratoe Oedjoe, Marcelien Dj; Rebhung, Felix (Jurnal Aquatik, 2023)
Cantang grouper (E. fuscoguttatus-lanceolatus) is a fish commodity with high economic value. Sargassum sp seaweed is a high source of nutrition because it contains protein, carbohydrates, fat in small quantities and ash content consisting of salt, sodium and potassium. This study aims to show how Sargassum sp is given and test how much the dose of Sargassum sp administration on the growth rate of grouper. The research was carried out from November 2021 to January 2022 at the Undana fishery pond, Semau. The results showed that different doses of Sargassum sp had a significant difference in influence on growth but did not have a difference in the effect on the survival of cantang grouper. The best dose applied in this study was 10% which was able to produce mitlak growth of 41.11 cm. However, the long growth of cantang grouper has no real effect.